2017
DOI: 10.13075/mp.5893.00620
|View full text |Cite
|
Sign up to set email alerts
|

Occupational cancers – Epidemiology and certification

Abstract: The etiology of cancer is multifactorial. Malignant tumors caused by factors occurring in the work environment, classified as carcinogenic in humans, can be recognized as an occupational disease. Analysis of epidemiological data indicates a significant underestimation of occupational cancer, mainly due to long latency period of these diseases. This publication provides guidance to certify occupational etiology of malignant tumors, based on the reviews of existing legislation and medical literature, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There are cancers known to be strongly associated with environmental factors present in the workplace [ 82 ]. The data are accumulating on the effects of chemicals on the development of PDAC, including exposure to pesticides, asbestos, benzene, and chlorinated hydrocarbons [ 83 ].…”
Section: Occupational Exposure and Physical Factorsmentioning
confidence: 99%
“…There are cancers known to be strongly associated with environmental factors present in the workplace [ 82 ]. The data are accumulating on the effects of chemicals on the development of PDAC, including exposure to pesticides, asbestos, benzene, and chlorinated hydrocarbons [ 83 ].…”
Section: Occupational Exposure and Physical Factorsmentioning
confidence: 99%
“…The etiology of neoplastic diseases is complex and multifaceted, conditioned by both external (environmental) and internal factors [4]. It has been shown that some behavioral and psychosocial factors (including stress and depression) as well as genetic predispositions may contribute to the development and progression of neoplastic diseases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%